People’s war, people’s press history and evolution of Ang Bayan (The People), the news organ of the Communist Party of the Philippines (CPP) - Tangi, Lucia P. (Plaridel, 2015)
Access online through this link: https://www.plarideljournal.org/article/peoples-war-peoples-press-history-and-evolution-of-ang-bayan-the-people-the-news-organ-of-the-communist-party-of-the-philippines-cpp